FORECASTING DRUG DEMAND USING THE SINGLE MOVING AVERAGE 3 PERIODE AT UGM ACADEMIC HOSPITAL - Ade Puspitasari; Satibi Satibi; Endang Yuniarti; Taufiqurohman Taufiqurohman (Universitas Muhammadiyah Magelang, 2022)
Drug management at the Academic Hospital of Gadjah Mada University found that the damaged and expired drugs amounted to 4.71% and the dead stock was 7.89%. One of the influential factors to contribute to the considerable amount of damaged and expired drugs and dead stock is inaccurate planning. Forecasting is one aspect of planning, which helps predict the upcoming event as a way to make planning more effective and efficient. One of the forecasting methods is the 3-period Single Moving Average (SMA). This study aims to forecast drug demand in January 2021 at the Academic Hospital of Gadjah Mada and to see the size of the error using the 3-period SMA method. This is an observational study with the retrsospective descriptive analysis. The research population is all drugs used at the Academic Hospital of Gadjah Mada in January 2018-December 2020. The samples are the top 5 most used drugs based on A category resulted from the ABC analysis of consumption in 2020 with certain criteria using purposive sampling technique. The drug demand was forecasted using Eviews 12 software and its error size, particularly the Mean Absolute Percentage Error (MAPE) was calculated using Microsoft Excel. The results showed that the forecast of drug demand in January 2021 was Tutofusin Ops 500ml 496pcs, Hemapo 2000 IU/ml 290pcs, Hemapo 3000 IU/ml 219pcs, Abilify Discmelt 10mg 717pcs, and Otsu-NS Piggyback 3736pcs. The calculated MAPE value was 8-32%, which means that the 3 period SMA forecasting is acceptable and reasonable for further application at the Academic Hospital of Gadjah Mada